1990
DOI: 10.1007/bf01420193
|View full text |Cite
|
Sign up to set email alerts
|

Linkage between O6-methylguanine-DNA methyltransferase (O6-MT) activity and cellular resistance to antitumour nitrosoureas in cultured rat brain tumour cell strains

Abstract: We have examined O6-methylguanine-DNA methyltransferase (O6-MT) activity of rat brain tumour cell strains with reference to cellular resistance to antitumour nitrosoureas, 1-(4-amino-2-methyl-5-pyrimidinyl)methyl-3-(2-chloroethyl)-3-nitrosourea hydrochloride (nimustine, ACNU) and methyl-6-[3-(2-chloroethyl)-3-nitrosoureido]-6-deoxy-alpha-D-glucopyrano side (ramustine, MCNU). The values of O6-MT activity were 52 and 160 fmol/mg protein extract in 9L and C6 rat brain tumour cells, respectively; while HeLa S3 cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

1991
1991
1996
1996

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…Xenografted C6-1 tumors which poorly responded to ACNU or MCNU exhibited higher 06-AT values (11). During some 10 years, drug sensitivity of the C6-1 cells in our stock to ACNU has been rather consistent with SDlO concentrations ranging between 50-80 pM (8,10,12). In contrast to the C6-1 cells, the C6-2 cells obtained from the JCRB were exceedingly sensitive to CENUs.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Xenografted C6-1 tumors which poorly responded to ACNU or MCNU exhibited higher 06-AT values (11). During some 10 years, drug sensitivity of the C6-1 cells in our stock to ACNU has been rather consistent with SDlO concentrations ranging between 50-80 pM (8,10,12). In contrast to the C6-1 cells, the C6-2 cells obtained from the JCRB were exceedingly sensitive to CENUs.…”
Section: Discussionsupporting
confidence: 55%
“…Rosenblum & Berger (9) suggested that more than one mechanism might be responsible for drug sensitivity, even in cell lines derived in a similar manner. Using rat glioma cell lines we showed a close correlation between O6-a1kylguanine-DNA alkyltransferase ( 06-AT) activity and resistance to antitumor CENUs (10). 9L cells with a low 06-AT activity were sensitive to ACNU, while C6-1 cells with a high activity were markedly resistant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The methods for measurement of the 06-AT activity were described elsewhere in detail (Mineura et al 1990). Briefly, frozen samples were cut into pieces on a block of dry ice.…”
Section: Methodsmentioning
confidence: 99%
“…Mer-tumors possess low activity of 06-AT enzyme and are substantially sensitive to chemotherapeutic alkylating agents. The 06-AT activity has been reported to correlate well with cellular resistance to antitumor CENUs, subject to chemotherapeutic alkylating agents in brain tumor cells and xenografted brain tumors (Schold et al 1989 ;Mineura et al 1990Mineura et al , 1991.…”
mentioning
confidence: 99%